2017
DOI: 10.1186/s13287-017-0498-1
|View full text |Cite
|
Sign up to set email alerts
|

p53 switches off pluripotency on differentiation

Abstract: The role of p53 as “a guardian of the genome” has been well established in somatic cells. However, its role in pluripotent stem cells remains much more elusive. Here, we discuss research progress in understanding the role of p53 in pluripotent stem cells and in pluripotent stem cell-like cancer stem cells. The p53 protein, which plays a key role in embryonic stem cells, was first discovered in 2005. Landmark studies of p53-related reprogramming elucidated this protein’s importance in induced pluripotent stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…Another study also demonstrated that ELPC recovered the transcriptional function of mutant p53 27 . Recent studies have confirmed that p53 regulates the differentiation of embryonic stem cells and induces pluripotent stem cells in response to genomic damage, similar to our results 28,29 .…”
Section: Discussionsupporting
confidence: 92%
“…Another study also demonstrated that ELPC recovered the transcriptional function of mutant p53 27 . Recent studies have confirmed that p53 regulates the differentiation of embryonic stem cells and induces pluripotent stem cells in response to genomic damage, similar to our results 28,29 .…”
Section: Discussionsupporting
confidence: 92%
“…gene sets involved in intestinal epithelial cell differentiationrelated genes were downregulated in both mutated TP53 cells, indicating that TP53WT might promote the differentiation of cancer cells. In normal cells, TP53WT has been suggested as a contributor to the process of switching off pluripotency upon differentiation (25), because TP53WT in the colon cancer cell might contribute to the transition of cancer stem cells to differentiated cancer cells. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…p53 is highly expressed in mouse ESCs in the cytoplasm under basal conditions (Aladjem et al 1998, Solozobova et al 2009 and functions to maintain genome stability in ESCs by inducing apoptosis upon DNA damage and differentiation (He et al 2016). p53 reduces reprogramming efficiency of somatic cells to pluripotent stem cells and its inhibition enhances reprogramming efficiency (reviewed in Lin & Lin 2017).…”
Section: Comparative Analysis Of Pluripotency Among Primates and Mousementioning
confidence: 99%